Efficacy and tolerability of moxidectin alone and in co-administration with albendazole and tribendimidine versus albendazole plus oxantel pamoate against Trichuris trichiura infections: a randomised, non-inferiority, single-blind trial. Issue 8 (August 2018) - Barda, Beatrice; Ame, Shaali M; Ali, Said M; Albonico, Marco; Puchkov, Maxim; Huwyler, Jörg; Hattendorf, Jan; Keiser, Jennifer
Summary: Background: The recommended anthelmintics show low efficacy in a single-dose regimen against Trichuris trichiura . Moxidectin, a new treatment for river blindness, might complement the drug armamentarium for the treatment and control of soil-transmitted helminthiasis. However, its efficacy against T trichiura has not yet been studied. The aim of the study was to assess the efficacy of moxidectin alone and in co-administrations against T trichiura infection. Methods: A randomised, single-blind, non-inferiority trial was done in two primary schools and one secondary school in Pemba, Tanzania. Adolescents aged 12–18 years who tested positive for T trichiura were randomly assigned (5:5:3:3) with a computer-generated sequence to receive moxidectin (8 mg) plus albendazole (400 mg), albendazole (400 mg) plus oxantel pamoate (25 mg/kg; reference treatment), moxidectin (8 mg) plus tribendimidine (200 mg or 400 mg), or moxidectin (8 mg) alone. Study group assignments were masked from participants and laboratory technicians. The primary outcome was non-inferiority with a 2 percentage point margin for egg reduction rate (ERR) against T trichiura assessed as the relative change in the geometric mean egg counts from baseline to 14–21 days after treatment with the Kato-Katz method, based on the available case population. Cure rates (CR) and tolerability (assessed 3, 24, and 48 h post treatment) were secondary outcomes. The study is registered at ISRCTN (number 20398469) and is closed to accrual. Findings: 701 students were enrolled between April 1, and Aug 7, 2017. Primary outcome data were available for 634 students. We observed ERRs of 98·5% for moxidectin plus albendazole and 99·8% for albendazole plus oxantel pamoate, resulting in an absolute difference of −1·2 percentage points (95% CI −1·8 to −0·8), meeting the non-inferiority margin. 100 (51%) of 197 students receiving moxidectin plus albendazole and 166 (83%) of 200 receiving albendazole plus oxantel pamoate were cured, indicating a difference of 32 percentage points (odds ratio 5·3, 95% CI 3·3 to 8·7). ERRs were 91·6% for moxidectin–tribendimidine and 83·2% for moxidectin. Only mild adverse events (mainly headache and stomach pain) were reported. The largest number of adverse events (126 [20%] of 632 students) was observed 24 h post treatment, with no difference among the individual treatment arms (ranging from 23 [19%] of 118 students treated with moxidectin to 38 [19%] of 199 with moxidectin plus albendazole). Interpretation: Moxidectin plus albendazole showed non-inferiority to albendazole plus oxantel pamoate in terms of ERR; however, albendazole plus oxantel pamoate showed a considerably higher cure rate. Dose-optimisation studies with moxidectin and moxidectin plus albendazole should be considered since the efficacy of the dose used for the treatment of onchocerciasis (8 mg) in this study might not be optimal for the treatment of T trichiura infections. Funding: Thrasher Foundation.